(untitled) - Dietel, Ronald J. (San Francisco, CA, 2006)
Going beyond mere strategies, Dietel, an assistant director at the National Center for Research on Evaluation, Standards and Student Testing, weighs in with a nine-point "learning model," designed to help students succeed in a test-centric academic environment. Though the model's pillars aren't groundbreaking (encourage your children, work with teachers, support healthy learning and study habits), the strength of Dietel's book lies in his detailed, yet readable, explanations of how, say, reading to children improves their communication and verbal skills. Each chapter is dedicated to a tenet of the "Get Smart" model and includes an overview, tips on implementing new habits (communication is key among them) and a mix of micro case-studies and real-world examples. Clear, concise writing, tried-and-true advice and the absence of testing jargon make this a handy go-to guide.
Keywords: Academic achievement,Learning,Education; Parent participation